The effect of Environmental, Social and Governance (ESG) and firm size on tax avoidance - Monica, Sindy; Ajimat, Ajimat (WIM Solusi Prima, 2024)
This research aims to test and analyze the influence of Environmental, Social and Governance (ESG) and Firm Size on Tax Avoidance. The study was conducted by analyzing the financial reports of companies in the LQ45 sector listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. The sample used in this study was 7 LQ45 sector companies during the period of 2018 to 2022 using purposive sampling technique. The data used in this study is secondary data in the form of financial reports from each company that has been used as a research sample and using a quantitative approach. The variables used in this study are Environmental, Social and Governance (X1) as the first independent variable, Firm Size (X2) as the second independent variable, and Tax Avoidance (Y) as the dependent variable. The research method used is quantitative, with data analysis, descriptive statistics, panel data linear regression and hypothesis testing, where no deviations were found and the results of this study test were normally distributed so that they meet the requirements for testing. Analysis of the research results using Eviews 12 Student Version Lite. The research results show that the best model is the Common Effect Model (CEM). The results of this study show that Environmental, Social and Governance (ESG) partially affects tax avoidance, as well as Firm Size partially affects tax avoidance and simultaneously Environmental, Social and Governance (ESG) and Firm Size on tax avoidance.